Plasma waveguides for high-intensity laser pulses - Spence, D; David James Spence (2001)
﻿ This thesis documents the development of plasma waveguides for high-intensity laser pulses. Initial work concentrated on the development of the discharge-ablated capillary waveguide, based on the work of A. Zigler (Zigler, A., Y. Ehrlich, C. Cohen, J. Krall and P. Sprangle, J. Opt. Soc. Am. B 13, 68). The waveguide was shown to be capable of guiding picosecond laser pulses with an intensity of 1016 W cm-2 over a length of 10 mm. The pulse energy transmission of the capillary was increased from 48% to 70% when the discharge was fired. An interferometry-based measurement technique was developed, allowing measurement of the electron density profile formed in the capillary waveguide. These measurements were used as input to a numerical simulation that predicted the propagation of intense laser pulses through partially-ionised plasma waveguides. Numerical simulations accurately reproduced the picosecond pulse guiding results, and gave important insights into the properties and severe drawbacks of partially-ionised waveguides. Previous work on partially-ionised plasma waveguides has not fully explored the implications of the propagation of intense pulses through the partially-ionised plasma. For polypropylene waveguides, it was shown that for pulses with an intensity of 1016 W cm-2, the waveguide is not capable of high-quality guiding. However, for pulses with an intensity of greater than 1017 W cm-2, high-quality guiding is predicted through the partially-ionised waveguide in a new regime called "quasi-matched guiding". A novel gas-filled capillary discharge waveguide was designed and built. The device was shown to form a guiding channel inside a capillary pre-filled with gas. Interferometry measurements of the electron density profile formed in a hydrogen-filled capillary discharge waveguide showed that an approximately parabolic plasma waveguide could be formed in an essentially fully-ionised hydrogen plasma. The device was used to guide femtosecond laser pulses, with an intensity of 1017 W cm-2, over distances of 20 and 40 mm, with a pulse energy transmission of 92% and 82% respectively. For the 20 mm-long waveguide, the peak intensity in the output plane of the waveguide was 70% of that at the waveguide input. These results indicate the lowest coupling and insertion losses of any waveguide published to date. The gas-filled capillary discharge waveguide is shown to be capable and versatile, and is suited for use as a tool in other applications. The use of the waveguide in the fields of XUV lasers and laser wakefield acceleration is discussed.